Monitoring digoxin therapy: II. Determinants of the apparent volume of distribution. - Aronson, J; Grahame-Smith, D (1977)
1 In eighteen subjects receiving digoxin therapy the apparent volume of distribution (Vd) of the drug has been calculated. 2 For each subject the sensitivity of the 86Rb transport mechanism of his pre-treatment erythrocytes to in vitro inhibition by digoxin has been measured (IC50). 3 The Vd of digoxin correlates both with the age of the patients and with the IC50 of their pre-treatment erythrocytes. 4 The implications of these findings are discussed in terms of the possible determinants of the Vd of digoxin. 5 Digoxin requirements may be predictable before therapy commences if IC50 measurements are performed.